Lentiviral vector–based xenograft tumors as candidate reference materials for detection of HER2-low breast cancer - Wei, Yali; An, Xu; Cao, Qinmei; Che, Nanying; Xue, Yuanyuan; Deng, Haiteng; Wang, Qingtao; Zhou, Rui (Frontiers in Oncology, 2022)
The human epidermal growth factor receptor 2 (HER2) is an important biomarker which plays a pivotal role in therapeutic decision-making for breast cancer (BC) patients. HER2-low BC patients can benefit from new HER2 targeted therapy. For ensuring the accurate and reproducible detection of HER2-low cancer, reliable reference materials are required for monitoring the sensitivity and specificity of detection assays. Herein, a lentiviral vector was used to transduce the HER2 gene into MDA-MB-231 cells that exhibited low HER2 density and the cells were characterized by droplet digital PCR (ddPCR) to accurately determine the copy number variation. Then, the formalin-fixed paraffin-embedded (FFPE) samples from xenografts were prepared and evaluated for suitability as candidate reference materials by immunohistochemistry (IHC) and fluorescence in situ hybridization (FISH). The FFPE reference materials were selected based on IHC score of 2+ and negative FISH result to meet the requirement for HER2-low BC detection. Furthermore, the FFPE reference materials exhibited typical histological structures which resembled the clinical BC specimens. These novel FFPE reference materials displayed the high stability and homogeneity, and they were produced in high quantity. In summary, we generated high-quality reference materials for internal quality control and proficiency testing in HER2-low detection.